2011
DOI: 10.1590/s0004-282x2011000700006
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depressive symptoms in clinically isolated syndrome and multiple sclerosis

Abstract: Depression and anxiety have been reported in patients with multiple sclerosis (MS) and in patients with clinically isolated syndrome (CIS). However, the precise mechanisms that lead to depressive and anxiety symptoms in these patients are still unclear. In this study we evaluated with the Beck Depression Inventory (BDI) and the Beck Anxiety Inventory (BAI) patients with MS and CIS and compared them to controls. We also correlated BDI and BAI scores with clinical parameters. Kruskall-Wallis followed by Dunn's M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
0
14
0
2
Order By: Relevance
“…Considering that CIS may be the first manifestation of MS and that the neuropathological abnormalities are the same only differing in intensity and distribution it seems reasonable that CIS may affect quality of life. It is possible that the impact of MS on quality of life is higher than in CIS since MS patients usually have higher neurological disability and higher rates of depression and anxiety 9 ; however, future studies are still needed to compare the reduction in quality of life in CIS and in MS patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that CIS may be the first manifestation of MS and that the neuropathological abnormalities are the same only differing in intensity and distribution it seems reasonable that CIS may affect quality of life. It is possible that the impact of MS on quality of life is higher than in CIS since MS patients usually have higher neurological disability and higher rates of depression and anxiety 9 ; however, future studies are still needed to compare the reduction in quality of life in CIS and in MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have shown that CIS patients may present mild cognitive impairment, especially in processing speed and executive functions [4][5][6] . Depression and anxiety have also been found in patients with CIS but their precise prevalence in this population is still unknown [6][7][8][9] . Quality of life has been studied in patients with multiple sclerosis (MS) but there are no previous studies evaluating quality of life in patients with CIS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All except one used standardised measures, and sample sizes ranged from n = 76 -1374 except for two (n = 18 and n = 45). Since this review, several other studies have confirmed this association (Anhoque, Domingues, Carvalho, Teixeira & Domingues, 2011;Arnett et al, 2008;Beal et al, 2007;da Silva et al, 2011;Gay et al, 2010;Sarısoy et al, 2013;Smith & Arnett, 2013).…”
Section: Introductionmentioning
confidence: 54%
“…Eleven CIS studies used five different instruments to assess depressive symptoms (Appendix 3) [44,60,69,[61][62][63][64][65][66][67][68]. The most frequently used questionnaire was BDI, which allowed for a meta-analysis of four studies (Table 2).…”
Section: Cismentioning
confidence: 99%